2010
DOI: 10.1086/656045
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi Sarcoma (KS)–Associated Herpesvirus MicroRNA Sequence Analysis and KS Risk in a European AIDS‐KS Case Control Study

Abstract: Background We recently identified polymorphisms in KSHV encoded microRNA (miRNA) sequences from clinical subjects. Here, we examine whether any of these may contribute to KS risk in a European AIDS-KS case control study. Methods KSHV viral load in peripheral blood was determined by real-time quantitative PCR. Samples that had detectable viral loads were used to amplify the 2.8 kbp microRNA encoding region plus a 646 bp fragment of the K12/T0.7 gene. Additionally, we characterized an 840 bp fragment of the K1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 60 publications
3
35
2
11
Order By: Relevance
“…Primer extension analysis also confirmed miR-K3ϩ1 expression in BC-1, VG-1, and BCLM cells, as previously reported (12). Interestingly, this SNP has been reported previously to be present in 3 of 19 analyzed KS patients, 13 of 23 KSHV-infected patients diagnosed with multicentric Castleman's disease (MCD), and 4 of 7 patients with KSHV-associated inflammatory cytokine syndrome, but its consequences for KSHV miRNA expression had not been explored (39,42,43).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Primer extension analysis also confirmed miR-K3ϩ1 expression in BC-1, VG-1, and BCLM cells, as previously reported (12). Interestingly, this SNP has been reported previously to be present in 3 of 19 analyzed KS patients, 13 of 23 KSHV-infected patients diagnosed with multicentric Castleman's disease (MCD), and 4 of 7 patients with KSHV-associated inflammatory cytokine syndrome, but its consequences for KSHV miRNA expression had not been explored (39,42,43).…”
Section: Resultssupporting
confidence: 72%
“…As expected, miR-K3ϩ1 and miR-23a expression resulted in comparable target repression, confirming that these miRNAs share their seed targets. miR-K3ϩ1 expression is not conserved among all KSHV isolates, however, implying that miR-K3ϩ1 is dispensable for the normal KSHV life cycle and also for the development of KS, MCD, PEL, and KSHV-associated inflammatory cytokine syndrome (39,42,43). We therefore explored the relationship between miR-23 and miR-K3, which is always expressed by KSHV.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we observed single-nucleotide polymorphisms (SNPs) in pre-microRNA sequences of miR-K12-2, -4, -5, -6, -7, -9, and -10 in clinical samples and PEL cell lines (15,16). The SNPs evaluated here are summarized in Table 1, which also indicates which SNPs were observed in clinical samples and which were also present in sequences from PEL cell lines.…”
Section: Comparative Expression Analysis Of Hek 293 Cells Transduced mentioning
confidence: 61%
“…2A). In our previous studies of KSHV microRNAencoded sequences in clinical samples, most subjects were observed to have the miR-K12-5 SNP (15,16). In contrast, SNPs within the terminal loop region of miR-K12-4 and -7 showed reduced expression.…”
Section: Comparative Expression Analysis Of Hek 293 Cells Transduced mentioning
confidence: 88%
See 1 more Smart Citation